Contract as assumption : the scholarship and influence of Professor Brian Coote - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 2011)
Summary of work by Brian Coote, ‘Contract as assumption - essays on a theme’ – nature of legal scholarship - relationship between Professor Coote and his scholarship – influence of Professor Coote.